(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Spectral painting The poetry of the poets in the Umayyad period, to be used in a remarkable way to express their heart’s pleasures and capabilities.This study examines the spectral painting, examines the motives that led to its evocation, and examines the general and special conditions that it produced such as psychological and coercive factors, temporal and spatial alienation, and other factors, and then shows its repercussions and goals. The spectrum combines family, and in it Salwa and Ta’al, Near the distance, and near the distance, but often leads to disappointment, it is a temporary journey in the place hit by the waves of life, or a beautiful dream of the poet, to wake him from the bitterness of reality, One of the most prominent findings of the research is that the spectral painting is a manifestation of a clear inability accompanied by the Umayyad poet, which was invented by the poets to suit their reality and circumstances, through which they expressed their feelings of longing and nostalgia for their homeland and their parents, so that they achieve stability or psychological balance or return to themselves.